"Skull on Fire": Monostotic Paget Disease of the Skull Bone. (January 2021) - Govers, Stefan; van der Zant, Friso M.; Wondergem, Maurits; Broos, Wouter A.M.; Knol, Remco J.J.
Abstract : Abstract: An 81-year-old woman was evaluated for a stroke. CT showed no intracranial abnormalities but diffuse patchy aspect of the neurocranium. An MRI and 18 F-NA PET/CT were performed to differentiate between metastases, Paget disease, hyperostosis frontalis interna, and primary malignancy. MRI yielded no additional findings. 18 F-NA PET/CT showed diffusely increased uptake in the skull and 4 spots with intense uptake. No other suspicious skeletal foci were seen elsewhere. Low-dose CT showed no sign of malignancy elsewhere. Image findings together with elevated serum alkaline phosphatase levels, slightly increased calcium levels, and normal phosphorus levels were interpreted as pathognomic for monostotic Paget.